DIGITAL TEACHING AWARENESS AND PRACTICE: NARRATIVES FROM INDONESIAN ESP TEACHERS - Arif Nugroho; Yunika Triana; Dewi Zulaiha (ELT Echo : The Journal of English Language Teaching in Foreign Language Context, 2022)
Research on the integration of digital technology in English language teaching has enormously been conducted. However, studies exploring digital teaching awareness and practice among English for specific purposes (ESP) teachers still remain a paucity of evidence. The present study aims to examine Indonesian ESP teachers’ digital teaching awareness and technology-based classroom activities. To reach the objective, qualitative approach under the procedure of narrative inquiry is applied. Semi-structured interview, observation, and document analysis are employed to obtain the required data from 14 Indonesian ESP teachers teaching at various fields of study. The results reveal that the Indonesian ESP teachers develop their digital teaching competence and awareness through professional training programs (e.g. joining workshop, seminar, and conference) and personal practice (e.g. learning from Youtube and other platforms). The results further depict that they utilize Social Networking Sites (e.g. Facebook, WhatsApp, and Instagram) and web-based materials (web-blog, Kahoot, Canva, and Edmodo) to assist their digital teaching practices. The results contribute to offering valuable insight and reference for English teachers to conduct interactive technology-based teaching and learning activities. In addition, the results can be used as a reference for school/college policymakers to ensure the efficacy of digital language learning practice.